2020
DOI: 10.1093/gbe/evaa135
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Invasions of Visitor, a DD41D Family of Tc1/mariner Transposons, throughout the Evolution of Vertebrates

Abstract: Although the DD41D (named as Visitor, VS) family of Tc1/mariner transposons was discovered in Arthropods, Mollusca and Ctenophora, the evolution profile of this family is still largely unknown. We found that VS is widespread in the animal kingdom, including 140 species of 18 orders in invertebrates and 30 species of 12 orders in vertebrates, and one land plant species. Our data revealed multiple horizontal transfer (HT) events in both invertebrates and vertebrates and invasion into multiple lineages of mammals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…On the other hand, the taxonomic distributions of Tc1/mariner families ( IT , TR , IC , and TRT ) in animals also revealed that they share some common hosts. Thus, some orders and species seem to be more hospitable to Tc1/mariner transposons than others, which has also been noted in a recent study [ 23 ]. The Actinopterygii and Anura tend to be more susceptible to the invasions of Tc1/mariner transposons, as all well-defined close sibling families of DD34E/ Tc1 ( IT , TR , IC and TRT ) were detected in these lineages.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…On the other hand, the taxonomic distributions of Tc1/mariner families ( IT , TR , IC , and TRT ) in animals also revealed that they share some common hosts. Thus, some orders and species seem to be more hospitable to Tc1/mariner transposons than others, which has also been noted in a recent study [ 23 ]. The Actinopterygii and Anura tend to be more susceptible to the invasions of Tc1/mariner transposons, as all well-defined close sibling families of DD34E/ Tc1 ( IT , TR , IC and TRT ) were detected in these lineages.…”
Section: Resultssupporting
confidence: 76%
“…To assess the distribution of IT among species, a TBLASTN search against all the available prokaryotic (archaea and bacteria) and eukaryotic (chromista, plantae, animalia, protozoa, and fungi) genomes placed at the NCBI database was performed using the sturgeon IT transposase sequence as the query. This revealed that IT has a restricted taxonomic distribution compared with the families of DD41D/VS [ 23 ] and DD37E/ TRT [ 20 ] of Tc1/mariner transposons, for which the taxonomic breadth has been well defined. Considerable hits encoding the preserved DD38E motifs were identified only in the animalia among eukaryotes, where ITs were present in 40 species of Arthropoda and one of the Cnidaria in invertebrates, one Agnathan species, one Anuran species, and 98 species in the Actinopterygii in vertebrates (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations